Does cultural heritage affect employment decisions: Empirical evidence for second generation immigrants in Germany - Anja Köbrich Leon (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2013)
The participation rate of women in the labor market shows a sizeable variation across countries and across time. Following studies conducted for North America, this section tests the hypothesis whether, next to structural conditions, cultural norms with regard to existing role models within society about working women influence a woman's participation decision. While using the epidemiological approach to economics, which aims to compare economic outcomes between immigrant groups to assess the role cultural factors may play, the persistence of heterogeneity in labor market outcomes across immigrant groups is used to assess the role cultural norms regarding working women may play in explaining differences in labor market outcomes between immigrant groups for first and second generation women in Germany. To overcome the problems associated with a qualitative proxy of culture, such as religiosity or ethnicity, the impact of culture on women working behavior is proxied by past female labor force participation (LFP) rates from the woman's country of origin or their parents, respectively. Using data from the GSOEP for the years 2001 to 2011, compared to findings from Fernández and Fogli (2009) and Gevrek et al 2011, which use large census data sets, I find statistically significant results for the association between cultural norms towards labor market behavior of women, as measured either by past female LFP in country of origin, country of origin indicator variables or attitudes towards working women prevalent in their home country, merely for first generation immigrants in Germany. However, while cultural heritage was found to play an inferior role for second generation immigrant women, religious identity, as a specific cultural trait, exhibits a strong negative relation with Muslim labor market behavior for both generations. .
Keywords: J15; J21; Z10; 330; female labor force participation; cultural norms; ethnicity; ethnic identity; religious identity